An Analysis of Students’ Perceptions and Learning Motivation in a Gamified Learning Management System - Adlan Nugroho; Prih Diantono Abda'u; Antonius Agung Hartono; Joko Purwanto (Politeknik Piksi Ganesha Indonesia, 2025)
The use of Learning Management Systems (LMS) in lectures is increasing, but student motivation to learn often poses a challenge. This study aims to examine the effect of gamification in LMS on student motivation to learn and to analyze the relationship between students' perceptions of gamification and their motivation levels. The study uses a quantitative design with measurements taken before and after the implementation of gamification, as well as correlation analysis to examine the relationship between variables. The results show that there is no significant difference between motivation before and after the implementation of gamification. However, perceptions of gamification are positively related to autonomy, connectedness, and achievement, which contribute to increased learning motivation. These findings indicate that gamification has an indirect effect through the reinforcement of psychological aspects that support intrinsic motivation.